The role of BRCA1 in non-small cell lung cancer - Gachechiladze, Mariam; Skarda, Josef (Biomedical papers, 2012)
Background. BRCA1 (Breast cancer 1) was previously identified as a breast and ovarian cancer susceptibility gene, but recently gained a major scientific interest as a prognostic and/or predictive marker for various tumors, including non-small cell lung cancer (NSCLC), which is the leading cause of cancer related mortality in the world. We aimed to review the role of BRCA1 in NSCLC based on currently available literature. Methods: We performed the literature search in Pubmed database, using key words: BRCA1, non small cell lung cancer, chemotherapy, drug resistance. Articles published in English were selected for review. Results: Research papers are mainly focused on BRCA1 mRNA expression studies in response to DNA damaging chemotherapy. Several articles about genetic and epigenetic changes of BRCA1 in NSCLC were also available. Conclusions: BRCA1 is a multifunctional tumor supressor protein, which plays a key role in essential cellular processes and modulates the cellular response to cytotoxic chemotherapy. With the difference from breast and ovarian cancer, BRCA1 has no role in NSCLC cancerogenesis and mainly discussed as a promising genomic marker for customized chemotherapy in NSCLC patients.
Keywords: BRCA1; non-small cell lung cancer; chemotherapy